2002
DOI: 10.1037/0022-3514.83.3.638
|View full text |Cite
|
Sign up to set email alerts
|

Stereotype performance boosts: The impact of self-relevance and the manner of stereotype activation.

Abstract: The activation of positive stereotypes has been shown to produce academic performance boosts. Evidence regarding the role of self-relevance in producing such effects has been mixed. The authors propose that the subtlety of stereotype activation plays a key role in creating performance boosts among targets and nontargets of stereotypes. Study 1 found that subtle stereotype activation boosted performance in targets, but blatant activation did not. Study 2 was conducted on both targets and nontargets using differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
209
1
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 224 publications
(235 citation statements)
references
References 47 publications
21
209
1
4
Order By: Relevance
“…Many stereotype threat studies report evidence of a small but noticeable increase in performance among the positively stereotyped group in the same condition that reduces the performance of those who are negatively stereotyped (Shih, Ambady, Richeson, Fujita, & Gray, 2002;Shih et al, 1999). Although it has seldom been significant in any given study, Walton and Cohen (2003) confirmed in a meta-analysis that this stereotype lift effect is reliable.…”
Section: Can This Model Also Explain Stereotype Lift Effects Stemmingmentioning
confidence: 93%
“…Many stereotype threat studies report evidence of a small but noticeable increase in performance among the positively stereotyped group in the same condition that reduces the performance of those who are negatively stereotyped (Shih, Ambady, Richeson, Fujita, & Gray, 2002;Shih et al, 1999). Although it has seldom been significant in any given study, Walton and Cohen (2003) confirmed in a meta-analysis that this stereotype lift effect is reliable.…”
Section: Can This Model Also Explain Stereotype Lift Effects Stemmingmentioning
confidence: 93%
“…Some studies testing students in the USA indicate that performance can also be shifted as an effect of priming (Shih et al 1999). Asian-American women primed with their Asian identity performed better on a math test, while participants primed with their female identity showed a decrease in performance, compared with women in a control group (Shih et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In general, however, stereotype threat is believed to result from increased concerns about being evaluated in terms of a negative group stereotype (Steele, 1997;Steele et al, 2002), whereas stereotype boost is believed to result from an ideomotor process in which the mere thought of an action, even if only at a nonconscious level, increases the tendency to engage in that action (Dijksterhuis, Bargh, & Zanna, 2001;Wheeler & Petty, 2001). Regardless of the underlying mechanisms, research has clearly demonstrated that the stereotype boost and stereotype threat effects occur when an environmental cue makes a group identity or the associated group stereotypes personally salient, ostensibly leading to the cognitive activation of that identity and the associated stereotypes (e.g., Shih et al, 2002;Steele & Aronson, 1995). Thus, factors that increase the tendency that a stereotyped identity will become personally salient and cognitively activated should increase susceptibility to these effects.…”
mentioning
confidence: 99%